PROPOSE MARKETING STRATEGY TO INCREASE NUMBER OF RETAIL INVESTOR (CASE STUDY: INDONESIA SEHAT MUTUAL FUND) - oktario pratama; Yudo Anggoro (Universitas Mercu Buana Yogyakarta, 2022)
The Indonesia Sehat Fixed Income Mutual Fund is a business innovation launched by BPJS Kesehatan through collaboration with three Investment Managers, namely PPT Bahana TCW Investment Management, PT Danareksa Investment Management, and PT Mandiri Manajemen Investasi. This product was created to help BPJS Kesehatan in achieving two targets, first to fulfill the OJK Regulation No. 1 of 2016 on investment of state securities for non-bank financial services institutions, and second to increase revenue collection with donation schemes through crowdfunding mechanisms.This research focuses on how BPJS Kesehatan can implement effective strategies to increase the number of retail investors in Indonesia Sehat mutual fund products. In this study, an external and internal analysis was used, using tools and frameworks such as PEST, Porter Five Forces, STP, VRIO, and supported by interviews and surveys to internal BPJS Kesehatan. Nex step is mapping the strengths, weaknesses, opportunities, and threats through the SWOT Matrix, as well as determining the root cause of the problems. From the results of the study, it was found that the root cause that hinders the growth of Indonesia Sehat mutual funds is the selection of segmentation and target investors that are too narrow combined with the very limited promotion of the products, and also cooperation that needs to be reviewed with three investment managers. Author recommends an evaluation of cooperation with the three existing investment managers, as well as changes in marketing strategies to increase the number of retail investors.